The dire effects of the lack of monetary and fiscal coordination - Francesco Bianchi; Leonardo Melosi (Federal Reserve Bank of Chicago, 2017)
What happens if the government's willingness to stabilize a large stock of debt is waning, while the central bank is adamant about preventing a rise in inflation? The large fiscal imbalance brings about inflationary pressures, triggering a monetary tightening, further debt accumulation, and additional inflationary pressure. Thus, the economy will go through a spiral of higher inflation, output contraction, and further debt accumulation. A coordinated commitment to inflate away the portion of debt resulting from a large recession leads to better macroeconomic outcomes by separating the issue of long-run fiscal sustainability from the need for short-run fiscal stabilization. This strategy can also be used to rule out episodes in which the central bank becomes constrained by the zero lower bound.
Keywords: E31; E52; E62; E63; D83; 330; Monetary and fiscal policies; coordination; emergency budget; Markov-switching models; liquidity traps; Geldpolitik; Finanzpolitik; Stabilisierungspolitik; Wirkungsanalyse; Konjunktur; Inflation; Niedrigzinspolitik